2021
DOI: 10.1136/bmjopen-2021-053587
|View full text |Cite
|
Sign up to set email alerts
|

Current practices and challenges in adaptation of clinical guidelines: a qualitative study based on semistructured interviews

Abstract: ObjectiveThis study aims to better understand the current practice of clinical guideline adaptation and identify challenges raised in this process, given that published adapted clinical guidelines are generally of low quality, poorly reported and not based on published frameworks.DesignA qualitative study based on semistructured interviews. We conducted a framework analysis for the adaptation process, and thematic analysis for participants’ views and experiences about adaptation process.SettingNine guideline d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
3
0
2
Order By: Relevance
“…There was an expectation on behalf of the authors that a larger number of qualitative studies would be found. There is an extensive field of qualitative enquiry on the implementation of other aspects of quality in health and social care such as clinical guidelines (242, 243) , quality improvement initiatives (244, 245) , patient feedback (246, 247) , and professional regulation. (248) Moreover, the regulation and compliance literature is replete with qualitative studies of organisational responses to regulation, yet very few examine organisations working in health and social care.…”
Section: Resultsmentioning
confidence: 99%
“…There was an expectation on behalf of the authors that a larger number of qualitative studies would be found. There is an extensive field of qualitative enquiry on the implementation of other aspects of quality in health and social care such as clinical guidelines (242, 243) , quality improvement initiatives (244, 245) , patient feedback (246, 247) , and professional regulation. (248) Moreover, the regulation and compliance literature is replete with qualitative studies of organisational responses to regulation, yet very few examine organisations working in health and social care.…”
Section: Resultsmentioning
confidence: 99%
“…There was an expectation on behalf of the authors that a larger number of qualitative studies would be found. There is an extensive field of qualitative enquiry on the implementation of other aspects of quality in health and social care such as clinical guidelines [ 244 , 245 ], quality improvement initiatives [ 246 , 247 ], patient feedback [ 248 , 249 ], and professional regulation [ 250 ]. Moreover, the regulation and compliance literature is replete with qualitative studies of organisational responses to regulation, yet very few examine organisations working in health and social care [ 236 ].…”
Section: Discussionmentioning
confidence: 99%
“…Existem diferentes modelos de adaptação de diretrizes, como ADAPTE (62), GRADE-ADOLOPMENT (63,64), o modelo do Royal College of Nursing (RCN) (65), RAPADAPTE (66), Dynamed (67) e o Systematic Guideline Review Method (68). Cada um apresenta uma abordagem com 8 a 12 etapas, com diferentes ferramentas e níveis de complexidade, a fim de identificar a confiabilidade das diretrizes que serviram de base para a adaptação e como os juízos de valor que levaram à formulação das recomendações podem ser aplicados a novas diretrizes adaptadas (6,69).…”
Section: Adaptação De Diretrizesunclassified